2003
DOI: 10.1128/iai.71.6.3603-3606.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Role for Extracellular Glutathione S -Transferase from Onchocerca volvulus Is the Production of Prostaglandin D 2

Abstract: The extracellular glutathione S-transferase from the filarial parasite Onchocerca volvulus (Ov-GST1) is a glutathione-dependent prostaglandin D synthase. Ov-GST1, located in the outer hypodermal lamellae and in parts of the cuticle, produces prostaglandin D 2 directly at the parasite-host interface. Ov-GST1 therefore has the potential to participate in the modulation of the host immune response by contributing to the production of prostanoids; this supports the predominant hypothesis that parasite-derived eico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 21 publications
1
40
0
2
Order By: Relevance
“…There are substantial information that DEC blocks a number of steps in both cyclooxigenase (COX) and lipoxigenase pathways, including inhibition of leucocyte chemotaxis, granulocyte degranulation, and peripheral vasodilation (Maizels and Denham 1992). Filarial parasites also synthesize and release prostanoids, particularly prostacyclin and PGE2, which are vasodilators and potent platelet anti-aggregatory factors (Liu et al 1990; Liu and Weller 1992;Sommer et al 2003). Moreover, KanesaThasan et al (1991) demonstrated that DEC severely inhibits the synthesis of microfilariae cyclooxigenase products.…”
Section: Introductionmentioning
confidence: 99%
“…There are substantial information that DEC blocks a number of steps in both cyclooxigenase (COX) and lipoxigenase pathways, including inhibition of leucocyte chemotaxis, granulocyte degranulation, and peripheral vasodilation (Maizels and Denham 1992). Filarial parasites also synthesize and release prostanoids, particularly prostacyclin and PGE2, which are vasodilators and potent platelet anti-aggregatory factors (Liu et al 1990; Liu and Weller 1992;Sommer et al 2003). Moreover, KanesaThasan et al (1991) demonstrated that DEC severely inhibits the synthesis of microfilariae cyclooxigenase products.…”
Section: Introductionmentioning
confidence: 99%
“…GSTs in general are multifunctional enzymes found in both invertebrates and vertebrates, and it is unlikely that all of the sigma-class forms will have PG synthase activity because some lack the amino acid residues involved in substrate (PGH 2 ) binding (Thomson et al, 1998). Recently, however, both the sigma class GSTs from the filarial parasite Onchocerca volvulus (Sommer et al, 2003) and Schistosoma (Johnson et al, 2003) have been shown to convert PGH 2 to PGD 2 , while in Ascaridia galli a purified GST has PGE synthase activity (Meyer et al, 1996). In the case of the O. volvulus GST (Ov-GST-1), this enzyme is located at the margins of the parasite, in the cuticle and hence in a prime location to influence the host responses.…”
Section: Prostanoid Biosynthetic Pathways In Invertebratesmentioning
confidence: 99%
“…Parasites not only induce prostaglandin production by the host to suppress the immune response, but also are able to produce prostaglandins themselves. Schistosomes were shown to secrete PGD2, thereby inhibiting the migration of Langerhans cells upon exposure to schistosome cercariae [31], and Onchocerca volvulus was shown to express glutathione S-transferase on its surface that produces PGD2 directly at the hostparasite interface [32]. The question regarding helminths is whether PGD2 production is involved in controlling anti-parasitic responses, which would justify the investment made by helminths to elaborate such antiinflammatory molecules.…”
Section: Induction Of Endogenous Immunomodulatory Lipids By Pathogensmentioning
confidence: 99%